"Cancer was a speed bump in my path to enlightenment:" A qualitative analysis of situational coping experiences among young adult survivors of childhood cancer. Issue 4 (4th July 2017) - Foster, Rebecca H.; Brouwer, Amanda M.; Dillon, Robyn; Bitsko, Matthew J.; Godder, Kamar; Stern, Marilyn
ABSTRACT: Young adult survivors of childhood cancer ( N = 47) completed essays exploring situational coping within a mixed methods study. Data were qualitatively analyzed using consensual qualitative research-modified methodology. Five themes emerged: (1) initial reactions to cancer, (2) adjustment/coping with cancer diagnosis and treatment, (3) provisions of social support, (4) perceived effects of cancer experience, and (5) reflections on the cancer experience. Perceptions of childhood cancer experiences appear generally positive, with the majority of negative reactions emerging immediately following diagnosis. Cognitive behavioral and supportive interventions may be most beneficial in the initial postdiagnosis period and should emphasize lasting benefits, accomplishments, and profound effects.